مقال معدل: ((أهمية المخطوط وكيفية التعامل معه للحفاظ على الموروث العربي)) - مولود, قاني; عبد العزيز, بوشلالق (جامعة الوادي - University of Eloued, 2021)
ملخص: تعدّ المخطوطات وعاء فكريا يحتوي على معالم التراث وأصوله عبر الأجيال، يحافظ على تراث الأمّة من كلّ تزييف أو تشويه، لذا اهتم بها الدارسون والمحقّقون والمؤرخون في الغرب والشرق، حيث كانت محور اهتمامهم ودراساتهم. إنّ ما حظيت به الأمة العربية الإسلامية من اهتمام بالمخطوطات، لم تحظ به أمم أخرى، لكثرة الإنتاج في مختلف المعارف والعلوم والفنون، ممّا يعدّ دليلا على شخصية الأمة العربية الثقافية المتنوع والمتفتح على الحضارات المختلفة. من هذا المنطلق جاءت هذه الدراسة للوقوف عند تلك الأهمية العظيمة للمخطوطات وكيفية تعامل الباحث الأكاديمي معها، حتى يسهل التعامل معها بطريقة علمية من جهة، والحفاظ على الموروث الثقافي من جهة ثانية. The manuscripts are an intellectual pot containing heritage features and origins across generations, preserving the nation's heritage from any falsification or distortion, so scholars, investigators, and historians in the West and East have taken an interest in them. The interest that the Arab Islamic nation has received in the manuscripts has not been heeded by other nations, owing to the large number of productions in different knowledge, sciences and arts. This is a demonstration of the diverse cultural personality of the Arab nation, which is open to different civilizations. From this point of view, this study comes to see the great importance of manuscripts and how academic researchers deal with them, so that they can be handled in a scientific way on the one hand, and the preservation of cultural heritage on the other
مقال
Keywords: المخطوط ـــ التراث ـــ التحقيق ــــ الباحث الأكاديمي.; Manuscript ـ heritage ـ academic researcher ـ investigation